Responsabilité sociétale des multinationales en Afrique Subsaharienne : enjeux et controverses - Youssoufou Hamadou Daouda (Éditions en environnement VertigO, 2014)
This paper proposes to shed light on the issues and controversies related to the practice of Corporate Social Responsibility (CSR) in sub-Saharan Africa. The paper shows that if multinationals CSR initiatives seek to enroll in a context of economic and social development, they prove to be very poor in terms of environmental requirements as well as social and economic achievements. The case of French nuclear group AREVA in Niger is proposed in illustration to show the gap between CSR strategies and the local environment in which multinational evolve (armed conflict, poverty, social inequalities, air pollution, degradation environment, groundwater contamination, etc.). Therefore, a dual challenge is needed. On the one hand, MNCs should strive to internalize negative externalities in their activities, and to participate in socio -economic projects that improve the quality of the social fabric. On the other hand, in cases where conflicts between multinational and stakeholders (civil society, government, NGOs, etc.) are strongly pronounced, public regulation of CSR (monitoring compliance with certain social and environmental standards, technical expertise, punitive measures, etc.) could help enroll more corporate actions in a process of socially responsible development.